2014
DOI: 10.1016/j.pharep.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oxycodone hydrochloride and three of its metabolites after intravenous administration in Chinese patients with pain

Abstract: Our pharmacokinetics of oxycodone injection in Chinese patients with pain strongly support continued development of oxycodone as an effective analgesic drug in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…2004; Hao et al. 2014; Kokubun et al. 2014) and goodness of fit of the two‐compartment analyses of the IV data to assess the intrinsic oxycodone distribution and clearance.…”
Section: Resultsmentioning
confidence: 99%
“…2004; Hao et al. 2014; Kokubun et al. 2014) and goodness of fit of the two‐compartment analyses of the IV data to assess the intrinsic oxycodone distribution and clearance.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [10] demonstrate oxycodone could provide superior analgesia to fentanyl but higher incidence of side effects, including PONV, dizziness, and drowsiness. Hao et al [11] have also shown that side effects of oxycodone hydrochloride include dizziness, nausea, vomiting, drowsiness, and fatigue. For the functional evaluation scores of the 3 groups, group C was the lowest, group A followed, and group B was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 42 Chinese patients who received IV oxycodone in doses of 2.5, 5, or 10 mg, the mean values of C max , AUC 0–6 , and AUC 0–∞ were dose‐dependent, but T max and T 1/2 were not . When patients received 0.5 mg/kg IV oxycodone, the volume of distribution at steady state was 2 to 3 L/kg with a clearance rate of 0.7 to 0.8 L/minute .…”
Section: Oxycodone Pharmacologymentioning
confidence: 99%
“…29,30 Table 1. Mean AUC 0-t ratios of oxycodone IV to metabolites from healthy volunteers in a study over three doses 32 Metabolite to Parent Drug Ratio (Over 3 Doses)…”
Section: Oxycodone Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation